Unsaturated polyester resin, putty composition using same, and coating method

By developing multifunctional chlorine-free disinfectants based on nanomaterials, the problem of poor improvement of existing chlorine-free disinfectants in high and low concentrations for human health and water quality is solved, and effective disinfection of various water sources at different concentrations is achieved.

JP7666888B2Active Publication Date: 2025-04-22KANSAI PAINT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2019048703
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-03-20
Filing Date
2019-03-15
Publication Date
2025-04-22
Estimated Expiration
2039-03-15

AI Technical Summary

Technical Problem

Existing chlorine-free disinfectants pose a potential threat to human health at high concentrations, and have no significant effect on improving water quality at low concentrations, making it difficult to meet the disinfection needs of different water source environments.

Method used

A multifunctional chlorine-free disinfectant based on nanomaterials has been developed to improve the efficiency and safety of the disinfectant through nanotechnology, so that it can effectively eliminate pathogens in water at different concentrations.

Benefits of technology

It has achieved effective disinfection of various water sources at different concentrations, reducing the potential risks to human health, and improving the water quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666888000001
    Figure 0007666888000001
  • Figure 0007666888000002
    Figure 0007666888000002
  • Figure 0007666888000003
    Figure 0007666888000003
Patent Text Reader

Abstract

To provide an unsaturated polyester resin and a putty composition that have an excellent drying property and that can form a putty layer having an extremely good adhesion even when the substrate is a galvanized steel sheet.SOLUTION: Provided is an unsaturated polyester resin and a putty composition in which, the acid value of the unsaturated polyester resin is in the range of 10 to 60 mgKOH / g, and, in the total acid components constituting the unsaturated polyester resin, a cyclic acid anhydride having a pKaof 5.8 or less is used by 1 to 50 mol% based on the total number of moles of all acid components.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an unsaturated polyester resin and a putty composition using the same. [Background technology]

[0002] Unsaturated polyester resins are generally relatively inexpensive compared to other resins, and have excellent workability as they harden in a short time even at room temperature. Furthermore, depending on the selection of the main raw material, they have a variety of excellent physical and chemical properties, so they are used in a variety of applications such as putty, paint, FRP molded products, resin concrete, and cast products.

[0003] In conventional putty compositions, styrene monomers have been used as reactive diluents for unsaturated polyester resins in terms of curing properties and physical properties. However, in recent years, styrene monomers have become subject to regulation under the Regulations for Prevention of Harm from Specified Chemical Substances, and there is a need to develop putty compositions that do not contain styrene, i.e., non-styrene type putty compositions.

[0004] As a non-styrene type putty composition (sometimes called a styrene-free putty composition), for example, Patent Document 1 discloses a putty composition using an unsaturated polyester resin composition in which hydroxyalkyl methacrylate is used as a reactive diluent instead of a styrene monomer. This composition has low odor and is excellent in hardening stability and surface drying, but when the substrate is a zinc-plated steel sheet, there are cases in which the adhesion, particularly the water-resistant adhesion, is significantly insufficient.

[0005] In addition, Patent Documents 2 and 3 disclose putty compositions containing a specific polymerizable unsaturated compound as a reactive diluent, a specific aromatic amine compound as a curing accelerator, and a rust inhibitor. Such compositions can form a putty layer that has good surface drying properties, has a good appearance without yellowing of the finished surface after topcoat painting, has excellent internal drying properties when applied thickly, and has excellent adhesion to both the substrate and the topcoat coating. However, when the substrate is a zinc-plated steel sheet, there are cases where the adhesion is insufficient.

[0006] A galvanized steel sheet is a steel sheet with a zinc plating applied to the surface thereof, and has excellent rust and corrosion resistance. In recent years, applications requiring durability such as long-term rust resistance, such as substrates for European cars and railway vehicles, may include hot-dip galvanized steel sheets with a large amount of zinc applied (basis weight) as part of the material. Generally, galvanized steel sheets are generally chemically treated with phosphoric acid or the like on the substrate surface in order to improve adhesion to the composition to be painted next and rust resistance. However, in order to reduce the number of steps, some galvanized steel sheets are not phosphate-treated, and when a putty composition is painted on a substrate including a galvanized steel sheet, the substrate may be subjected to a surface treatment such as polishing, and the chemical treatment layer may be scraped off. In this case, when a putty layer is formed on a galvanized steel sheet using a putty composition containing a conventional unsaturated polyester resin, there is a problem that adhesion failure such as peeling and blisters occurs frequently from the base point between the galvanized steel sheet and the putty composition layer.

[0007] Patent Document 4 discloses an unsaturated polyester resin composition for paint, which is characterized by blending a specific amount of unsaturated carboxylic acid with a composition consisting of an air-drying unsaturated polyester resin, a filler, and a vinyl monomer in specific ratios for the purpose of improving adhesion to zinc plating. When this composition is used, adhesion to zinc-plated steel sheets is slightly improved, but water-resistant adhesion in particular is insufficient. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2005-162830 A [Patent Document 2] JP 2005-206781 A [Patent Document 3] JP 2006-206863 A [Patent Document 4] Special Publication No. 06-102753 Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present invention is to provide an unsaturated polyester resin and a putty composition which are free of styrene monomer, have excellent drying properties, and can form a putty layer having extremely excellent adhesion even when the substrate is a zinc-plated steel sheet. [Means for solving the problem]

[0010] As a result of intensive research to solve the above problems, the present inventors have found that a putty layer having excellent adhesion (particularly water-resistant adhesion) can be obtained by incorporating a specific amount of a specific cyclic acid anhydride into the polybasic acid component of an unsaturated polyester resin, and have arrived at the present invention.

[0011] That is, the present invention includes the following aspects.

[0012] Item 1. An unsaturated polyester resin having an acid value of 10 to 60 mgKOH / g, which comprises an acid component (a) containing a cyclic acid anhydride (a1) having a pKa2 of 5.8 or less and a hydroxyl group-containing component (b) as constituent units, the unsaturated polyester resin being a polyester resin having a radically polymerizable unsaturated group, a carboxyl group, and a hydroxyl group; The unsaturated polyester resin (A) is characterized in that the amount of the cyclic acid anhydride (a1) having a pKa2 of 5.8 or less used is within the range of 1 to 50 mol % based on the total number of moles of the acid component (a).

[0013] Item 2. The unsaturated polyester resin (A) according to Item 1, wherein a cyclic acid anhydride (a1) having a pKa2 of 5.8 or less is used as an acid source for the carboxyl group of the unsaturated polyester resin (A).

[0014] Item 3. The unsaturated polyester resin (A) according to item 1, wherein the acid component (a) further contains methyltetrahydrophthalic acid and / or its anhydride.

[0015] Item 4. The unsaturated polyester resin (A) according to any one of Items 1 to 3, wherein the acid component (a) contains an unsaturated polybasic acid and a saturated polybasic acid in a molar ratio of unsaturated polybasic acid / saturated polybasic acid within a range of 99 / 1 to 50 / 50.

[0016] Item 5. The unsaturated polyester resin (A) according to any one of Items 1 to 4, wherein the unsaturated polyester resin (A) is a resin obtained by reacting a polyester intermediate (X) having a carboxyl group and a hydroxyl group with a cyclic acid anhydride (a1) having a pKa2 of 5.8 or less.

[0017] Item 6. A putty composition comprising the unsaturated polyester resin (A) according to any one of items 1 to 5.

[0018] Item 7. A putty composition comprising the unsaturated polyester resin (A) according to any one of Items 1 to 6 and a polymerizable unsaturated compound (B), wherein the polymerizable unsaturated compound (B) contains a secondary hydroxyl group-containing polymerizable unsaturated monomer (b1) as a component thereof.

[0019] Item 8. The putty composition according to item 7, containing 10 to 200 parts by mass of the component (b1) per 100 parts by mass of the resin solid content of the unsaturated polyester resin (A).

[0020] Item 9. The putty composition according to any one of items 6 to 8, comprising a dehydrating agent (C).

[0021] Item 10. The putty composition according to any one of items 6 to 9, containing hollow particles (E).

[0022] Item 11. A coating method for forming a putty layer by coating a putty composition according to any one of items 6 to 10 on a substrate surface. Item 12. The coating method according to item 11, wherein the substrate surface is any one substrate surface selected from the group consisting of bullet train cars, railway cars, and automobile cars. Effect of the Invention

[0023] The unsaturated polyester resin of the present invention, particularly when used as a putty composition, can dramatically improve adhesion to galvanized steel sheets without maintaining or impairing drying properties, paint workability (pot life), and other coating properties, and can provide a stable putty layer with excellent coating durability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The unsaturated polyester resin (A) of the present invention has a specific acid value and contains a specific amount of a specific cyclic acid anhydride, and is particularly suitable for use in putty compositions. The unsaturated polyester resin (A) of the present invention will now be described in detail.

[0025] <<Unsaturated polyester resin (A)>> The unsaturated polyester resin (A) of the present invention is characterized in that it has as its constituent units a specific acid component (a) and a hydroxyl group-containing component (b), and uses as the acid component (a) 1 to 50 mol % of a cyclic acid anhydride (a1) having a pKa2 of 5.8 or less, based on the total number of moles of the acid component (a).

[0026] [Cyclic acid anhydride (a1) with pKa2 of 5.8 or less] In the present invention, a cyclic acid anhydride is a compound having one or more cyclic carboxylic anhydride structures in a molecule. A cyclic carboxylic anhydride structure is a structure in which a compound having two or more carboxyl groups in one molecule is subjected to intramolecular dehydration condensation to form a ring. When a cyclic acid anhydride is used as the acid component (a), a carboxyl group can be stably introduced into the side chain or end of the polyester polymer chain of the unsaturated polyester resin (A) by the ring-opening reaction of the acid anhydride (hereinafter sometimes referred to as half-esterification reaction), and this is preferable because it improves adhesion to a substrate, particularly water-resistant adhesion.

[0027] The cyclic acid anhydride (a1) having a pKa2 of 5.8 or less that can be applied to the unsaturated polyester resin (A) of the present invention is a compound that can form a cyclic carboxylic acid anhydride structure by intramolecularly dehydrating a polybasic acid having a pKa2 of 5.8 or less, the smaller the acid dissociation exponent pKa value, and the stronger the acidity, and generally, the pKa2 value of the second dissociation stage is greater than the pKa1 value of the first dissociation stage, but in the present invention, it is important that the acid dissociation exponent pKa2 of the second stage is 5.8 or less.

[0028] In the present invention, by using a cyclic acid anhydride (a1) constituting the unsaturated polyester resin (A) having a pKa2 value of 5.8 or less, it is possible to exhibit excellent adhesion to the substrate surface, particularly to a galvanized steel sheet. The lower limit of the pKa2 value is not particularly limited, but it is preferably a value exceeding 0.

[0029] The pKa2 value is given by Brown, HC et al., in Braude, EA and FC Nachod Determination of Organic Structures by Physical Methods, Academic Press, New York, 1955, and if not described therein, it can be determined by potentiometric titration.

[0030] Specific examples of the cyclic acid anhydride (a1) having a pKa2 of 5.8 or less include succinic anhydride, tetrahydrophthalic anhydride, bromomaleic anhydride, phthalic anhydride, chloromaleic anhydride, malonic anhydride, glutaric anhydride, adipic anhydride, suberic anhydride, and azelaic anhydride. From the standpoints of storage stability, water-resistant adhesion, cost, and the like, at least one selected from succinic anhydride and phthalic anhydride is preferred.

[0031] The content of the cyclic acid anhydride (a1) having a pKa2 of 5.8 or less is within the range of 1 to 50 mol %, and more preferably 2 to 40 mol %, based on the total number of moles of the acid component (a) from the viewpoint of adhesion to the substrate surface, particularly to a zinc-plated steel sheet.

[0032] As the acid source of the carboxyl group in the unsaturated polyester resin (A), it is preferable to use a cyclic acid anhydride (a1) having a pKa2 of 5.8 or less.

[0033] [Acid component (a)] In the present invention, the acid component (a) constituting the unsaturated polyester resin (A) is a compound having one or more acid groups in the molecule, and examples of such compounds include polybasic acids, fatty acids, and rosin acids.

[0034] Specifically, a polybasic acid is a compound having two or more acid groups such as carboxylic acid in one molecule. In the present invention, acid anhydrides are also included in the polybasic acid.

[0035] Polybasic acids are classified into unsaturated polybasic acids and saturated polybasic acids depending on whether they have a radically polymerizable unsaturated group.

[0036] In the present invention, it is suitable that the acid component (a) contains a cyclic acid anhydride (a1) and also contains an unsaturated polybasic acid. By containing an unsaturated polybasic acid as a part of the acid component (a), a radically polymerizable unsaturated group can be introduced into the unsaturated polyester resin (A), and the drying property can be improved.

[0037] [Unsaturated polybasic acid (containing radically polymerizable unsaturated groups in the molecule)] The unsaturated polybasic acid is a compound having a functional group having a carbon-carbon double bond exhibiting radical polymerizability in the molecule and two or more acid groups, and examples thereof include maleic acid, fumaric acid, itaconic acid, tetrahydrophthalic acid, tetrabromophthalic acid, tetrachlorophthalic acid, HET acid, himic acid, and methyltetrahydrophthalic acid (methyltetrahydrophthalic acid has isomers depending on the position of the methyl group and the double bond). For example, cis-3-methyl-4-cyclohexene-cis,cis-1,2-dicarboxylic acid (hereinafter sometimes abbreviated as β-PMAA), trans-3-methyl-4-cyclohexene-cis,cis-1,2-dicarboxylic acid, cis-3-methyl-4-cyclohexene-cis,trans-1,2-dicarboxylic acid, trans-3-methyl-4-cyclohexene-cis,trans-1,2-dicarboxylic acid, 4-methyl-Δ4-tetrahydrophthalic anhydride (structural isomer of 3-methyl-Δ4-tetrahydrophthalic anhydride), etc. can be mentioned] and their anhydrides, etc., and from the viewpoint of surface drying property, it is preferable to contain methyltetrahydrophthalic acid and / or its anhydride, especially β-PMMA (cis-3-methyl-4-cyclohexene-cis,cis-1,2-dicarboxylic acid and / or its anhydride). In addition, from the viewpoint of curing property inside the coating film, it is preferable to use fumaric acid or maleic acid, especially fumaric acid in combination.

[0038] When methyltetrahydrophthalic acid and / or its anhydride are used as the unsaturated polybasic acid component, the amount used is preferably within the range of 1 to 50 mol %, 2 to 45 mol %, and further preferably 3 to 40 mol %, based on the total number of moles of the acid component (a).

[0039] [Saturated polybasic acid (no radically polymerizable unsaturated groups in the molecule)] The saturated polybasic acid is a compound having two or more acid groups but not a functional group having a carbon-carbon double bond exhibiting radical polymerization in the molecule, and examples thereof include phthalic acid, phthalic anhydride, halogenated phthalic anhydride, isophthalic acid, terephthalic acid, hexahydrophthalic acid, hexahydrophthalic anhydride, hexahydroterephthalic acid, hexahydroisophthalic acid, succinic acid, malonic acid, glutaric acid, adipic acid, sebacic acid, 1,12-dodecane diacid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid anhydride, 4,4'-biphenyldicarboxylic acid, and dialkyl esters thereof.

[0040] The above-mentioned unsaturated polybasic acids or saturated polybasic acids can be used alone or in combination of two or more.

[0041] In the present invention, the content ratio of the unsaturated polybasic acid and the saturated polybasic acid constituting the unsaturated polyester resin (A) can be appropriately adjusted within a molar ratio of 99 / 1 to 50 / 50 (unsaturated polybasic acid / saturated polybasic acid), preferably within a range of 96 / 4 to 60 / 40, from the viewpoints of surface drying property and water resistance.

[0042] [Hydroxyl group-containing component (b)] The hydroxyl-containing component (b) which is the reaction partner of the acid component (a) constituting the unsaturated polyester resin (A) of the present invention is a compound having one or more hydroxyl groups in the molecule, specifically, a polyhydric alcohol having two or more hydroxyl groups in the molecule, a hydroxy compound having an allyl ether group, etc.

[0043] [Polyhydric alcohol] Examples of the polyhydric alcohol include polyols such as alkane polyols, oxyalkylene polyols, polyoxyalkylene polyols, and alicyclic polyols. Specific examples of the glycol include ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, 2-methyl-1,3-propanediol, 1,3-butanediol, neopentyl glycol, hydrogenated bisphenol A, 1,4-butanediol, 1,6-hexanediol, 1,9-nonanediol, bisphenol compounds, adducts of bisphenol compounds such as bisphenol A with alkylene oxides such as propylene oxide and ethylene oxide, 1,2,3,4-tetrahydroxybutane, glycerin, trimethylolpropane, 1,3-propanediol, 1,2-cyclohexane glycol, 1,3-cyclohexane glycol, 1,4-cyclohexane glycol, 1,4-cyclohexanedimethanol, paraxylene glycol, bicyclohexyl-4,4'-diol, 2,6-decalin glycol, 2,7-decalin glycol, and bishydroxyethyl terephthalate. These may be used alone or in combination of two or more.

[0044] The unsaturated polyester resin (A) may contain the polyhydric alcohol in an amount of 40 to 70 mol %, preferably 45 to 60 mol %, based on the total number of moles of the acid component (a) and the hydroxyl group-containing component (b).

[0045] [Hydroxy Compound Having Allyl Ether Group] In the present invention, from the viewpoint of improving surface drying properties, it is preferable to use a radically polymerizable hydroxy compound, particularly a hydroxy compound having an allyl ether group, as the hydroxyl group-containing component (b).

[0046] The hydroxy compound having an allyl ether group is a compound having at least one allyl ether group in one molecule, and examples thereof include ethylene glycol monoallyl ether, diethylene glycol monoallyl ether, triethylene glycol monoallyl ether, polyethylene glycol monoallyl ether, propylene glycol monoallyl ether, dipropylene glycol monoallyl ether, tripropylene glycol monoallyl ether, polypropylene glycol monoallyl ether, 1,2-butylene glycol monoallyl ether, 1,3-butylene glycol monoallyl ether, hexylene glycol monoallyl ether, octylene glycol monoallyl ether, trimethylolpropane diallyl ether, glycerin diallyl ether, and pentaerythritol triallyl ether.

[0047] The unsaturated polyester resin (A) can contain a hydroxy compound having an allyl ether group in an amount of 1 to 30 mol %, preferably 3 to 20 mol %, based on the total mole number of the acid component (a) and the hydroxyl group-containing component (b).

[0048] When a hydroxy compound having an allyl ether group is used as the hydroxyl group-containing component in producing the unsaturated polyester resin (A), it may be mixed with the polyhydric alcohol in advance or may be added later to cause a condensation reaction.

[0049] In addition, as the acid component (a) and the hydroxyl group-containing component (b), other acid components and hydroxyl group-containing components other than those mentioned above can be used as necessary. Such other acid components are not particularly limited, and examples thereof include saturated fatty acids, unsaturated fatty acids, rosin, etc., and other hydroxyl group-containing components are not particularly limited, and examples thereof include monoalcohols such as methyl alcohol, ethyl alcohol, propyl alcohol, butyl alcohol, 2-ethylbutanol, 2-ethylhexanol, stearyl alcohol, and 2-phenoxyethanol; propylene oxide, butylene oxide, and alcohol compounds obtained by reacting a monoepoxy compound such as "Cardura E10P" (trade name, manufactured by Momentive Specialty Chemicals, glycidyl ester of synthetic highly branched saturated fatty acid) with an acid, etc.

[0050] The reaction ratio between the acid component (a) and the hydroxyl group-containing component (b) is preferably adjusted such that the content of the hydroxyl group-containing component (b) is 1.0 to 1.25 mol per 1 mol of the acid component (a).

[0051] The unsaturated polyester resin (A) of the present invention is a polyester resin having a radically polymerizable unsaturated group, a carboxyl group, and a hydroxyl group, and it is suitable to use a cyclic acid anhydride (a1) having a pKa2 of 5.8 or less as an acid source for the carboxyl group of the unsaturated polyester resin (A). In particular, it is preferable that the unsaturated polyester resin (A) is a resin obtained by reacting a polyester intermediate (X) having a carboxyl group and a hydroxyl group with a cyclic acid anhydride (a1) having a pKa2 of 5.8 or less.

[0052] <Method for producing unsaturated polyester resin (A)> The method for producing the unsaturated polyester resin (A) is not particularly limited, but a preferred method is, for example, a production method including a step of reacting an acid component (a) with a hydroxyl group-containing component (b) to obtain a polyester intermediate (X) having a carboxyl group and a hydroxyl group, and then a step of reacting the polyester intermediate (X) with a cyclic acid anhydride (a1) having a pKa2 of 5.8 or less.

[0053] The polyester intermediate (X) can be obtained by a known method for producing a polyester resin, specifically, it can be produced by subjecting the acid component (a) and the hydroxyl group-containing component (b) to a condensation reaction.

[0054] The condensation reaction for producing the polyester intermediate (X) may be carried out in one stage by charging the acid component (a) and the hydroxyl group-containing component (b) all at once, or may be carried out in multiple stages by dividing the materials into two or more batches. When the reaction for producing the polyester intermediate (X) is carried out in multiple stages, the types and amounts of the acid component (a) and the hydroxyl group-containing component (b) used can be appropriately adjusted.

[0055] In the present invention, the cyclic acid anhydride (a1) having a pKa2 of 5.8 or less is used as an essential component to obtain the unsaturated polyester resin (A) into which a relatively high acid strength and active carboxyl group is stably introduced. Therefore, when such unsaturated polyester resin (A) is used as a putty composition, it has an effect of providing excellent water-resistant adhesion to substrates, particularly to zinc-plated steel sheets, which are poorly adherent substrates.

[0056] In the present invention, the cyclic acid anhydride (a1) having a pKa2 of 5.8 or less may be used at any stage of the production of the unsaturated polyester resin (A) as long as the amount used is within the range of the present invention, but it is suitable to use it as a production raw material at the stage of half-esterification reaction with the polyester intermediate (X) from the viewpoint of improving water-resistant adhesion to the substrate. It is presumed that the unsaturated polyester resin (A) obtained by such a production method can efficiently arrange carboxyl groups having relatively strong acid strength at the terminal and / or side chain of the polymer chain of the polyester intermediate (X). That is, the amount of the cyclic acid anhydride (a1) used in the half-esterification reaction is preferably within the range of 1 to 30 mol%, more preferably within the range of 2 to 20 mol%, based on the total mole number of the acid component (a).

[0057] In the present invention, in the production of the unsaturated polyester resin (A) and the polyester intermediate (X), a polycondensation catalyst, a heavy metal oxide, and a polymerization inhibitor may be used as necessary. The temperature condition during the condensation reaction for producing the polyester intermediate (X) is preferably within the range of 150 to 250°C, and more preferably within the range of 160 to 200°C, from the viewpoint of preventing gelation. In addition, the heating temperature condition during the half-esterification reaction of the polyester intermediate (X) and the acid anhydride (a1) is preferably within the range of 80°C to 150°C, and more preferably within the range of 100 to 140°C, from the viewpoint of production stability.

[0058] In the present invention, the acid value of the unsaturated polyester resin (A) is within the range of 10 to 60 mgKOH / g, preferably 12 to 50 mgKOH / g, and more preferably 15 to 40 mgKOH / g, from the viewpoint of improving water resistance.

[0059] When the unsaturated polyester resin (A) is obtained by a half-esterification reaction, the acid value of the polyester intermediate (X) before the half-esterification is preferably within a range of 3 to 50 mgKOH / g, and more preferably 5 to 40 mgKOH / g. Here, the acid value in this specification is a value expressed in mg of the mass of potassium hydroxide required to neutralize the protonic acid contained in 1 g of the resin, and can be measured in accordance with JIS K-6901 (2008) Testing methods for liquid unsaturated polyester resins.

[0060] Moreover, the hydroxyl value of the unsaturated polyester resin (A) of the present invention is preferably within a range of 5 to 100 mgKOH / g, more preferably 20 to 80 mgKOH / g, and even more preferably 35 to 80 mgKOH / g, from the viewpoint of water-resistant adhesion.

[0061] When the unsaturated polyester resin (A) is obtained by half-esterification, the hydroxyl value of the polyester intermediate (X) before half-esterification is preferably in the range of 20 to 120 mgKOH / g, and more preferably in the range of 40 to 100 mgKOH / g, from the viewpoint of production stability. Here, the value of the hydroxyl value in this specification is a calculated value based on the blend amount (mgKOH / g resin).

[0062] The weight average molecular weight (Mw) of the unsaturated polyester resin (A) described above is preferably within the range of 1,000 to 100,000, more preferably 2,000 to 50,000. In the present invention, the weight average molecular weight is a value measured by gel permeation chromatography and converted into polystyrene. As the gel permeation chromatograph device, "HLC8120GPC" (manufactured by Tosoh Corporation, product name) can be used, and as the columns used therein, four columns, "TSKgelG-4000H×L", "TSKgelG-3000H×L", "TSKgelG-2500H×L", and "TSKgelG-2000H×L" (all manufactured by Tosoh Corporation, product names), can be used. Here, tetrahydrofuran was used as the mobile phase, the measurement temperature was 40° C., the flow rate was 1 cc / min, and an RI refractometer was used as the detector.

[0063] <<Putty composition>> In the present invention, the unsaturated polyester resin (A) can be used to prepare a putty composition. The putty composition of the present invention contains the specific unsaturated polyester resin (A) and a polymerizable unsaturated compound (B).

[0064] <Polymerizable unsaturated compound (B)> The polymerizable unsaturated compound (B) is a compound other than the unsaturated polyester resin (A) and has one or more polymerizable unsaturated groups in the molecule. The polymerizable unsaturated group means an unsaturated group capable of radical polymerization. Examples of such polymerizable unsaturated groups include vinyl groups, (meth)acryloyl groups, and (meth)allyl groups. Here, the term "(meth)acryloyl group" means an acryloyl group or a methacryloyl group, and the term "(meth)allyl group" means an allyl group or a methallyl group.

[0065] From the viewpoint of water-resistant adhesion, it is particularly preferable that the polymerizable unsaturated compound (B) contains a secondary hydroxyl group-containing polymerizable unsaturated monomer (b1).

[0066] Examples of the secondary hydroxyl group-containing polymerizable unsaturated monomer (b1) include polymerizable unsaturated monomers having a secondary hydroxyl group with 2 to 8 carbon atoms, particularly 3 to 6 carbon atoms, and more particularly 3 or 4 carbon atoms in the alkyl group of the ester moiety, such as 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 3-hydroxybutyl (meth)acrylate; and adducts of (meth)acrylic acid and epoxy group-containing compounds (e.g., Cardura E10, product name, manufactured by Hexion Specialty Chemical Co., Ltd., neodecanoic acid glycidyl ester). Among these, 2-hydroxypropyl (meth)acrylate is particularly preferred from the viewpoints of water resistance and water-resistant adhesion.

[0067] In the case where the unsaturated group-containing polyester resin (A) of the present invention and the secondary hydroxyl group-containing polymerizable unsaturated monomer (b1) as the polymerizable unsaturated compound (B) are contained in a putty composition, the putty composition can suppress odor after application to a substrate, while maintaining the coating hardness and surface drying property, and improving water-resistant adhesion, which is particularly preferable.

[0068] Examples of hydroxyl group-containing polymerizable unsaturated monomers other than the component (b1) include monoesters of (meth)acrylic acid and dihydric alcohols having 2 to 10 carbon atoms (excluding those having a secondary hydroxyl group), such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; and hydroxyl group-containing polymerizable unsaturated monomers (excluding those having a secondary hydroxyl group) modified by ring-opening polymerization reaction of ε-caprolactone.

[0069] Specific examples of other polymerizable unsaturated compounds include aromatic vinyl compounds such as vinyl toluene, t-butyl styrene, and divinyl benzene; (meth)acrylic acid ester compounds of monohydric alcohols such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isobornyl (meth)acrylate, norbornyl (meth)acrylate, and adamantyl (meth)acrylate; trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 2-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, 2,2-bis(4-(3-methacryloxy-2-hydroxypropoxy)-phenyl)propane, di(methacryl)-2-propanediol, and the like. (Meth)acrylic acid ester compounds of polyhydric alcohols such as 2,2-bis(4-methacryloxyethyl)trimethylhexamethylene diurethane and 2,2-bis(4-methacryloxypolyethoxyphenyl)propane; hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate (excluding the secondary hydroxyl group-containing polymerizable unsaturated monomers listed in the previous section (b1)); ethylene glycol dimaleate, propylene glycol diitaconate, etc.; 4-(meth)acryloyloxy group-containing aromatic polycarboxylic acids and their acid anhydrides such as 4-(meth)acryloyloxymethoxycarbonyl phthalic acid and 4-(meth)acryloyloxyethoxycarbonyl phthalic acid; allyl compounds such as diallyl phthalate, diallyl isophthalate, and triallyl phthalate; epoxy (meth)acrylates; polyester (meth)acrylates; polydimethylsilicone di(meth)acrylates; urethane (meth)acrylates;Polyfunctional (meth)acrylates having a heterocyclic structure such as tris(2-(meth)acryloyloxyalkyl)isocyanurate, dicyclopentenyl group-containing polymerizable unsaturated compounds such as dicyclopentenyloxyethyl acrylate, dicyclopentenyloxyethyl methacrylate, dicyclopentenyloxypropyl (meth)acrylate, and dicyclopentenyl (meth)acrylate, cyclohexanedimethanol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, hydrogenated bisphenol A, Examples of the monofunctional and / or polyfunctional (meth)acrylates include monofunctional and / or polyfunctional (meth)acrylates having an alicyclic structure such as aryl A di(meth)acrylate, difunctional (meth)acrylates having an aromatic ring derived from a diepoxy compound or diol compound having a bisphenol skeleton, naphthalene skeleton or biphenyl skeleton, or monofunctional and / or polyfunctional (meth)acrylates having a cyclic structure such as modified products of these polyfunctional (meth)acrylates with ethylene oxide, propylene oxide, caprolactone, etc., which can be used alone or in combination of two or more. Among the monofunctional and / or polyfunctional (meth)acrylates having a cyclic structure, monofunctional and / or polyfunctional (meth)acrylates having a cyclic structure without a hydroxyl group in the molecule are particularly preferred from the viewpoint of water resistance.;

[0070] Here, "(meth)acrylate" means acrylate or methacrylate, "(meth)acrylic acid" means acrylic acid or methacrylic acid, "(meth)acryloyl" means acryloyl or methacryloyl, and "(meth)acrylamide" means acrylamide or methacrylamide.

[0071] The content of the polymerizable unsaturated compound (B) is suitably 10 to 200 parts by mass, preferably 40 to 120 parts by mass, based on 100 parts by mass of the resin solid content of the unsaturated polyester resin (A).

[0072] When the polymerizable unsaturated compound (B) contains the component (b1), the content thereof is preferably within a range of 10 to 200 parts by mass, more preferably 40 to 80 parts by mass, per 100 parts by mass of the resin solid content of the unsaturated polyester resin (A).

[0073] <Dehydrating Agent (C)> The putty composition of the present invention preferably contains a dehydrating agent (C). By containing the dehydrating agent (C), the putty layer can be prevented from decreasing in surface dryness, water resistance, and adhesion over time, and a putty composition of stable quality can be obtained. Although it is not intended to restrict the present invention, it is considered that the dehydrating agent (C) appropriately adjusts the water content in the composition, prevents the putty layer from decreasing in surface dryness, water resistance, and adhesion over time, and a putty composition of stable quality can be obtained. As the dehydrating agent (C), conventionally known inorganic dehydrating agents and organic dehydrating agents can be used without any restrictions.

[0074] Specific examples of inorganic dehydrating agents include calcium compounds such as calcium hydride, calcium oxide (quicklime), calcium chloride, calcium sulfate (gypsum), etc.; barium compounds such as barium oxide, etc.; magnesium compounds such as magnesium sulfate, etc.; sodium compounds such as sodium sulfate, sodium carbonate, etc.; copper compounds such as copper sulfate, etc.; inorganic silicon compounds such as silica gel, etc.; and aluminum compounds such as aluminum oxide (hydraulic alumina, lithium aluminum hydride, non-crystalline silica alumina, crystalline aluminosilicates (molecular sieves), etc.

[0075] Specific examples of organic dehydrating agents include alkyl orthoformate, alkyl orthoacetate, alkyl orthoborate, vinylsilane, alkoxysilane compounds, monoisocyanate compounds, aliphatic diisocyanate compounds, alicyclic diisocyanate compounds, aromatic diisocyanate compounds, trivalent or higher organic polyisocyanate compounds, dimers or trimers of these polyisocyanate compounds, prepolymers obtained by subjecting these polyisocyanate compounds to a urethane reaction with a polyhydric alcohol, a low molecular weight polyester resin or water under conditions of excess isocyanate groups, aliphatic acid anhydrides such as acetic anhydride, aromatic acid anhydrides such as benzoic anhydride, carbodiimide compounds such as N,N'-dicyclohexylcarbodiimide and 1-ethyl-3(3-dimethylaminopropyl)carbodiimide hydrochloride, etc. The above-mentioned examples can be used alone or in combination of two or more.

[0076] The amount of the dehydrating agent (C) is preferably within a range of 0.1 to 50 parts by mass, more preferably 2 to 30 parts by mass, based on 100 parts by mass of the total of the unsaturated polyester resin (A) and the polymerizable unsaturated compound (B).

[0077] <Polyvalent metal compounds (D)> The putty composition of the present invention is suitable for containing a polyvalent metal compound (D). By containing the polyvalent metal compound, it is possible to form a putty layer having excellent water resistance and adhesion. The polyvalent metal compound means a compound containing a polyvalent metal having a valence of 2 or more (other than monovalent).

[0078] Specific examples of the polyvalent metal compound (D) include metal oxides such as zinc oxide, calcium oxide, magnesium oxide, aluminum oxide, iron oxide, and copper oxide; metal carbonates such as magnesium carbonate, calcium carbonate, and zinc carbonate; and metal hydroxides such as calcium hydroxide, zinc hydroxide, aluminum hydroxide, and magnesium hydroxide.

[0079] In the present invention, the polyvalent metal compound is preferably a compound containing an element of Group 2 of the Periodic Table, in particular, magnesium.

[0080] When such a polyvalent metal compound (D) is contained, the content thereof is suitably 0.1 to 50 parts by mass, preferably 5 to 30 parts by mass, based on 100 parts by mass of the total mass of the unsaturated polyester resin (A) and the polymerizable unsaturated compound (B).

[0081] The putty composition of the present invention may contain a curing accelerator and / or a polymerization inhibitor in order to adjust the curing rate.

[0082] <Curing accelerator> By including a curing accelerator, the curing property may be further improved in some cases. As the curing accelerator, any conventionally known one may be used without any particular limitation, but aromatic amines are particularly preferred from the viewpoints of curing property and drying property. Specifically, N,N-substituted anilines such as aniline, N,N-dimethylaniline, N,N-diethylaniline, p-toluidine, N,N-dimethyl-p-toluidine, N,N-bis(2-hydroxyethyl)-p-toluidine, 4-(N,N-dimethylamino)benzaldehyde, 4-[N,N-bis(2-hydroxyethyl)amino]benzaldehyde, 4-(N-methyl-N-hydroxyethylamino)benzaldehyde, N,N-bis(2-hydroxypropyl)-p-toluidine, N-ethyl-m-toluidine, m-toluidine, pyridine, phenylmorpholine, piperidine, N,N-bis(hydroxyethyl)aniline, and diethanolaniline, N,N-substituted-p-toluidines, 4-(N,N-substituted amino)benzaldehyde, and 4-dimethyl dimethylaminobenzoic acid, ethyl 4-dimethylaminobenzoate, (n-butoxy)ethyl 4-dimethylaminobenzoate, isoamyl 4-dimethylaminobenzoate, 2-ethylhexyl 4-dimethylaminobenzoate, 3-dimethylaminobenzoic acid, ethyl 3-dimethylaminobenzoate, (n-butoxy)ethyl 3-dimethylaminobenzoate, isoamyl 3-dimethylaminobenzoate, 2-ethylhexyl 3-dimethylaminobenzoate, 2-dimethylaminobenzoic acid, ethyl 2-dimethylaminobenzoate, (n-butoxy)ethyl 2-dimethylaminobenzoate, isoamyl 2-dimethylaminobenzoate, 2-ethylhexyl 2-dimethylaminobenzoate, and other dimethylamino group-containing benzoic acids, which can be used alone or in combination of two or more.

[0083] Furthermore, among such aromatic amines, compounds having a dimethylamino group are preferred because they cause less yellowing of the topcoat film applied on the putty composition. Among these, 4-dimethylaminobenzoic acid and 3-dimethylaminobenzoic acid are particularly suitable.

[0084] When an aromatic amine is contained, the content thereof is desirably within a range of 0.01 to 2.0 parts by mass, preferably 0.05 to 1.5 parts by mass, relative to 100 parts by mass of the unsaturated polyester resin (A) from the viewpoints of pot life (gelation time), air drying properties and polishability of the formed coating film, and heat yellowing resistance of the topcoat coating film.

[0085] Examples of the curing accelerator other than the aromatic amine include metal driers such as cobalt naphthenate, copper naphthenate, barium naphthenate, cobalt octylate, manganese octylate, zinc octylate, and vanadium octylate; aliphatic amines such as triethanolamine and diethylenetriamine other than the aromatic amines listed above, tertiary amines, and quaternary ammonium salts, which can be used alone or in combination of two or more. When using a curing accelerator other than the aromatic amine, the amount is suitably in the range of 0.01 to 5 parts by mass relative to 100 parts by mass of the unsaturated polyester resin (A).

[0086] As the polymerization inhibitor, for example, those mentioned in the section on the polymerization inhibitor for the unsaturated polyester resin (A) can be suitably used.

[0087] <Coloring pigments> The putty composition of the present invention may contain a coloring pigment. Examples of the coloring pigment include inorganic pigments such as titanium white, red iron oxide, carbon black, iron black, and zinc oxide; and organic pigments such as molybdenum red, Prussian blue, cobalt blue, azo pigments, phthalocyanine pigments, quinacridone pigments, isoindoline pigments, threne pigments, perylene pigments, dioxazine pigments, and diketopyrrolopyrrole pigments. These coloring pigment components can be used alone or in combination of two or more.

[0088] The color pigment is preferably an inorganic pigment, and preferably contains titanium white, because it can provide color with a relatively small amount of use and also because of the ease of polishing and the finish when used as a putty.

[0089] When the above-mentioned color pigment is used, its content is not particularly limited as long as the desired design can be obtained. For example, the content is within a range of 1 to 100 parts by mass, preferably 1 to 50 parts by mass, per 100 parts by mass of the total mass of the unsaturated polyester resin (A) and the polymerizable unsaturated compound (B).

[0090] <Extender pigment> The putty composition of the present invention may contain an extender pigment.

[0091] Examples of the extender pigment include talc, mica, barium sulfate, kaolin, calcium carbonate, clay, silica, quartz, and glass. Hollow particles (E) may also be included. These extender pigment components can be used alone or in combination of two or more. From the viewpoints of polishing workability, finish, and cost in putty applications, the extender pigment is preferably at least one selected from talc, barium sulfate, kaolin, clay, silica, and calcium carbonate, and particularly preferably contains talc.

[0092] When the above-mentioned extender pigment is used, its content is preferably within the range of 1 to 300 parts by mass, more preferably 70 to 250 parts by mass, per 100 parts by mass of the total of the unsaturated polyester resin (A) and the polymerizable unsaturated compound (B), from the viewpoints of polishing workability and finishing properties in putty applications.

[0093] <Hollow particles (E)> Among the body pigments, it is preferable to contain hollow particles (E) since this has the effect of reducing the weight of the putty layer obtained and improving the sanding workability and water-resistant adhesion.

[0094] The hollow particles (E) (hollow particles are sometimes called balloons) are not particularly limited, and examples thereof include resin foam particles such as expanded polystyrene particles, expanded polyethylene particles, expanded polypropylene particles, and expanded polyurethane; inorganic foam particles such as perlite, volcanic gravel, and baked vermiculite; resin-based hollow particles such as acrylic resin, styrene resin, acrylic-styrene copolymer resin, acrylic-acrylonitrile copolymer resin, acrylic-styrene-acrylonitrile copolymer resin, acrylonitrile-methacrylonitrile copolymer resin, acrylic-acrylonitrile-methacrylonitrile copolymer resin, and vinylidene chloride-acrylonitrile copolymer resin; inorganic balloons such as glass balloons such as silica balloons and shirasu balloons, and ceramic balloons such as alumina silica balloons; and organic-inorganic composite balloons in which the surfaces of the resin-based hollow particles are modified with inorganic materials such as silica, alumina, and calcium carbonate. These may be used alone or in combination of two or more.

[0095] In particular, from the viewpoints of polishability and water-resistant adhesion, shirasu balloons and organic-inorganic composite balloons modified with an inorganic material are preferred.

[0096] When the hollow particles (E) are used, the content thereof is preferably within the range of 1 to 20 parts by mass, more preferably 2 to 10 parts by mass, per 100 parts by mass of the total mass of the unsaturated polyester resin (A) and the polymerizable unsaturated compound (B), from the viewpoints of polishing workability and finishing properties in putty applications.

[0097] <Rust inhibitor> The putty composition of the present invention may contain a rust inhibitor.

[0098] Examples of the rust inhibitor include phosphate-based agents such as zinc phosphate, calcium phosphate, zinc phosphite, potassium phosphite, and calcium phosphite; polyphosphate-based agents such as aluminum dihydrogen tripolyphosphate; molybdate-based agents such as zinc molybdate and calcium molybdate, and phosphomolybdate-based agents such as aluminum phosphomolybdate; borate-based agents; metaborate-based agents such as barium metaborate; zinc calcium cyanamide-based agents; modified silica in which cations such as calcium, zinc, cobalt, lead, strontium, and barium are bound to porous silica particles, ion-exchanged silica in which cations are bound by ion exchange; aluminum pyrophosphate-based agents; and rust-preventive pigments such as zinc oxide, as well as 1-(benzothiazol-2-ylthio)succinic acid, (2-benzothiazol-2-ylthio)succinic acid di-(C12-14 alkyl)ammonium salts. and organic rust inhibitors such as benzothiazole compounds such as tungium salts; and ketocarboxylic acid compounds such as the addition product of 4-methyl-γ-oxo-benzenebutanoic acid and N-ethylmorpholine, and the addition product of 4-methyl-γ-oxo-benzenebutanoic acid and zirconium. These can be used alone or in combination of two or more.

[0099] When a rust inhibitor is contained, the content thereof is preferably in the range of 0.1 to 50 parts by mass, and more preferably 5 to 45 parts by mass, per 100 parts by mass of the total mass of the unsaturated polyester resin (A) and the polymerizable unsaturated compound (B), from the viewpoints of the polishing workability and finishing properties of the putty layer, the curing property and drying property, the spatula application property, and the heat yellowing resistance, etc.

[0100] The putty composition of the present invention may contain other additives, such as organic solvents, ultraviolet stabilizers, ultraviolet absorbers, low-shrinkage agents, antioxidants, anti-skinning agents, plasticizers, aggregates other than the hollow particles, flame retardants, stabilizers, reinforcing materials, viscosity regulators such as viscosity reducers, pigment dispersants, modifying resins, thixotropic agents, thixotropic assistants, defoamers, leveling agents, silane coupling agents, and aldehyde scavengers.

[0101] The putty composition of the present invention can provide a putty layer having good workability with a spatula and excellent physical properties even without substantially blending an organic solvent. However, from the viewpoint of viscosity adjustment, the putty composition may contain an organic solvent such as ethyl acetate, butyl acetate, acetone, methyl ethyl ketone, methanol, ethanol, propanol, butanol, toluene, or xylene.

[0102] The composition containing the above-mentioned unsaturated polyester resin (A) and polymerizable unsaturated compound (B) can be used as the base agent of a putty composition. The viscosity of the putty composition can be appropriately adjusted depending on the intended use of the putty composition. In terms of thick application, spatula application, and surface finish, the viscosity is generally within the range of 100 to 2,000 Pa·sec, preferably 200 to 1,300 Pa·sec.

[0103] In this specification, the viscosity of the putty composition is measured using a Brookfield viscometer "VISCOMETER TV-22" (product name, manufactured by Toki Sangyo Co., Ltd.) by adjusting the temperature of the sample to 25°C, using a No. 7 rotor and a rotation speed of 2 rpm.

[0104] The putty composition of the present invention may be a multi-component system having a component containing the unsaturated polyester resin (A) and the polymerizable unsaturated compound (B) as a main component and a component containing an organic peroxide as a curing agent component.

[0105] Specific examples of the organic peroxide that can be used include conventionally known organic peroxides such as diacyl peroxides, peroxy esters, hydroperoxides, dialkyl peroxides, ketone peroxides, peroxy ketals, alkyl peresters, and percarbonates, and these may be used alone or in combination of two or more.

[0106] The content of the organic peroxide is not particularly limited and can be appropriately adjusted depending on the coating environment and the physical properties of the coating film, but is preferably within the range of 0.1 to 6 parts by mass per 100 parts by mass of the total mass of the unsaturated polyester resin (A) and the polymerizable unsaturated compound (B).

[0107] The putty composition of the present invention may be a two-component system consisting of a main component and a hardener component. In this case, if the putty composition contains a dehydrating agent (C), a polyvalent metal compound (D), a hardening accelerator, a coloring pigment, an extender pigment, a polymerization inhibitor, etc. as necessary, they can be contained in the main component.

[0108] The putty composition of the present invention may be a multi-component system consisting of three or more components, including a main component, a hardener component, and other components such as a dehydrating agent (C), a polyvalent metal compound (D), a hardening accelerator, a coloring pigment, an extender pigment, a polymerization inhibitor, etc. For example, when a water-reactive dehydrating agent is contained as the dehydrating agent (C), it may be blended into either the main component or the crosslinking agent, but from the viewpoints of storage stability and coating workability, it is preferable to use a three-component system in which the main component, hardener, and dehydrating agent are mixed together just before use.

[0109] As described above, even if the putty composition does not contain styrene, a putty layer excellent in surface drying property and internal hardening property can be obtained, and it can be provided as a non-styrene type putty composition (styrene-free putty composition), but it does not exclude the inclusion of styrene.

[0110] <Base material> The substrate surface to which the putty composition of the present invention can be applied is not particularly limited, and examples thereof include metal material surfaces such as iron, zinc, aluminum, brass, copper, tinplate, stainless steel, galvanized steel, zinc alloys (Zn-Al, Zn-Ni, Zn-Fe, etc.), plated steel, and aluminum alloys, as well as chemically treated surfaces thereof, various plastic materials, and composite materials thereof.

[0111] The application of the putty composition of the present invention is not particularly limited, but it is useful for new painting or repair painting of painted bodies of railway vehicles such as bullet trains and electric trains, and repair painting of painted bodies of vehicles such as automobiles, etc., because of its excellent paint workability and water-resistant adhesion, etc. In particular, it is preferable to use any one selected from bullet train vehicles, railway vehicles, and automobile vehicles as the substrate surface.

[0112] <<Painting method>> The putty composition can be applied to a substrate surface to form a putty layer.

[0113] The putty composition can be applied using, for example, a spatula.

[0114] Before applying the putty composition, the portion of the substrate to be coated may be subjected to a surface preparation such as cleaning or sanding.

[0115] The method for drying the putty composition includes, for example, room temperature drying or forced drying, and the coating film can be cured to the inside by this drying process. In the case of room temperature drying, specifically, the composition is left to stand at room temperature (about 5 to 40°C) for 5 hours or more, or in the case of forced drying, the composition can be heated at 40°C to 120°C for 5 to 60 minutes. In the case of forced drying, the composition can be set (left to stand) at room temperature for 2 to 30 minutes before heat curing in consideration of the finish.

[0116] The putty layer thus obtained may be polished, and the polishing method can be, for example, using waterproof paper or sandpaper.

[0117] A paint composition such as a base paint composition may be further applied on the polished surface after the putty layer obtained is polished. The paint composition that may be applied on the putty layer may be any of the commonly used organic solvent-based, water-based, powder-based undercoat paints, colored base paints, top clear paints, etc., such as acrylic lacquer, acrylic melamine resin paint, two-liquid type urethane curing paint containing a hydroxyl group-containing resin and a polyisocyanate compound, acid-epoxy curing paint, fluororesin paint, alkyd resin paint, alkyd melamine resin paint, and polyester melamine resin paint, which are not particularly limited.

[0118] By using the putty composition containing the unsaturated polyester resin (A) of the present invention, it is possible to form a putty layer having extremely excellent adhesion even when the substrate is a zinc-plated steel sheet, and further, the putty layer has excellent adhesion to both the substrate and the topcoat coating film, and has excellent finish. EXAMPLES

[0119] The present invention will be further described below with reference to examples. In the following, "parts" and "%" mean "parts by mass" and "% by mass", respectively.

[0120] (Example 1) Unsaturated polyester resin No. 1 In a 2-liter four-neck flask equipped with a stirrer, nitrogen gas inlet tube, water separator, thermometer and reflux condenser, 1.35 mol of phthalic anhydride (*1), 3.15 mol of fumaric acid (*5), 4.75 mol of diethylene glycol and 0.63 mol of trimethylolpropane diallyl ether were charged, and heating was started while blowing in nitrogen gas. Dehydration condensation reaction was carried out at an internal temperature of 190°C, and when the acid value reached 20 mgKOH / g, 0.25 mol (5 mol% of the total acid components) of phthalic anhydride (*1) for half esterification was added, and half esterification reaction of the anhydride was carried out at an internal temperature of 130°C, and 0.33 g of methylhydroquinone was added to obtain unsaturated polyester resin No. 1 with an acid value of 30 mgKOH / g. The acid value, hydroxyl value and weight average molecular weight of the obtained unsaturated polyester resin No. 1, as well as the acid value and hydroxyl value before half esterification are shown in Table 1. Among the acid components blended when producing unsaturated polyester resin No. 1, the proportion of cyclic acid anhydride (a1) having a pKa2 of 5.8 or less was 34 mol % based on the total moles of all acid components.

[0121] (Examples 2 to 6 and Comparative Examples 1 to 6) Unsaturated polyester resins Nos. 2 to 12 Unsaturated polyester resins Nos. 2 to 12 were obtained in the same manner as in Example 1, except that the blending was as shown in Table 1. For those that did not undergo half-esterification reaction, the (a1) component was not added, and the subsequent steps were carried out in the same manner to obtain unsaturated polyester resins.

[0122] [Table 1]

[0123] The * in Table 1 and the Examples is as follows.

[0124] (*1) Phthalic anhydride (abbreviated as PA in the table): A cyclic acid anhydride (a1) with a pKa2 of 5.8 or less, a saturated polybasic acid, molecular weight 148.10, pKa2=5.41, (*2) Succinic anhydride (abbreviated as SA in the table): A cyclic acid anhydride (a1) with a pKa2 of 5.8 or less, a saturated polybasic acid, molecular weight 100.07, pKa2=5.48, (*3)β-PMMA: cis-3-methyl-4-cyclohexene-cis,cis-1,2-dicarboxylic anhydride, cyclic acid anhydride with pKa2 of 5.8 or more, unsaturated polybasic acid, molecular weight 166.17, (*4) Hexahydrophthalic anhydride: A cyclic acid anhydride with a pKa2 of more than 5.8 (Hexahydrophthalic Anhydride, abbreviated as HHPA in the table), an unsaturated polybasic acid, with a molecular weight of 154.17. (*5) Fumaric Acid (abbreviated as FA): Unsaturated polybasic acid, molecular weight 116.07, (*6) Maleic anhydride (abbreviated as MA in the table): A cyclic acid anhydride with a pKa2 of not less than 5.8, an unsaturated polybasic acid, with a molecular weight of 98.10 and a pKa2 of 6.23.

[0125] (Examples 7 to 25 and Comparative Examples 7 to 12) Each component was mixed and stirred with each unsaturated polyester resin obtained in the above Examples and Comparative Examples so as to obtain the composition shown in Table 2-1, and mixed and dispersed for 20 minutes with a high-speed kneader to obtain each main component. 2% by mass of a hardener component containing 30 parts of cyclohexanone peroxide and 70 parts of an ester-based organic solvent was added to each main component and mixed uniformly by hand stirring to obtain putty compositions (P-1) to (P-25). The pot life of each putty composition was evaluated and the results are shown in Table 2-1.

[0126] <Creating test panels> Each of the putty compositions obtained above was applied to one surface of a substrate with a spatula, smoothed out, and coated to a thickness of 2 mm to prepare a test coated plate, and the surface drying property, coating film hardness (Martens strength), and abrasion property were evaluated. The results are shown in Table 2-2.

[0127] The following substrates were used:

[0128] Substrate 1: A hot-dip galvanized steel sheet (thickness 0.8 mm, no chemical conversion treatment) was used, the surface of which was lightly polished with waterproof paper #240 to provide the substrate surface.

[0129] Substrate 2: A mild steel plate, "SPCC-SB" (product name, manufactured by Nippon Test Panel Co., Ltd.), was used. The surface of this was lightly polished with waterproof sandpaper #240, and this was used as the substrate surface.

[0130] Substrate 3: A stainless steel plate, "SUS#304" (product name, manufactured by Paltec Co., Ltd.), was used, the surface of which was lightly polished with waterproof sandpaper #240 to serve as the substrate surface.

[0131] Substrate 4: An aluminum steel plate, "A5052P" (product name, manufactured by Paltec Co., Ltd.), was used. The surface of this was lightly polished with waterproof sandpaper #240, and this was used as the substrate surface.

[0132] <Creating topcoat painted boards> The test coated plates coated with each of the putty compositions obtained above were left to dry at room temperature (20°C) for 6 hours to form a putty layer, and then the coating surface was lightly polished with #400 waterproof paper, and "Retan PG80 White Base" (trade name, acrylic polyol and polyisocyanate-based topcoat paint, manufactured by Kansai Paint Co., Ltd.) was spray-painted on the putty layer to a dry film thickness of 50 μm, and dried at 60°C for 30 minutes to prepare coated plates with topcoat coating films formed on each putty layer, which were then subjected to a water immersion test [water resistance (blister evaluation) and adhesion]. The results are shown in Table 2-2.

[0133] The compounding composition of each putty composition is shown in Table 2-1, and the results of the corresponding evaluation tests are shown in Table 2-2. The amount of unsaturated polyester resin shown in Table 2-1 is expressed as solid content.

[0134] [Table 2-1]

[0135] The * in Table 2 is as follows.

[0136] (*7) Ethoxylated bisphenol A dimethacrylate (EO: 2.3 moles): (Product name: NK Ester BPE-80N, average ethoxylated mole number 2.3 moles), manufactured by Shin-Nakamura Chemical Co., Ltd., a dimethacrylate with a cyclic structure that does not have a hydroxyl group in the molecule. (*8) Ethoxylated bisphenol A dimethacrylate (EO: 10 moles): (Product name: NK Ester BPE-500, average ethoxylated mole number 10 moles), manufactured by Shin-Nakamura Chemical Co., Ltd., a dimethacrylate having a cyclic structure without a hydroxyl group in the molecule, (*9) Tricyclodecane dimethanol dimethacrylate: (Product name: NK Ester DCP), manufactured by Shin-Nakamura Chemical Co., Ltd., a dimethacrylate with a cyclic structure that does not have a hydroxyl group in the molecule.

[0137] (*10) Hollow particles: Silafine (registered trademark) MSB-301, product name, manufactured by Axes Chemical Co., Ltd., Shirasu Balloon (inorganic hollow particles), average particle diameter 50 μm.

[0138] (*11) Pot life (painting workability): The putty compositions, which were prepared by uniformly mixing each base agent with a hardener, were left at room temperature (20°C) for a specified period of time, then hand-stirred again to mix uniformly, and the putty compositions were applied to the substrate surface with a spatula. The time until the spatula application became difficult (defective), such as spreading, breaking, or difficulty in handling the spatula, was measured and evaluated. S: If left for 10 minutes or more, the putty composition begins to show an increase in viscosity, but if left for less than 10 minutes, there is no problem with the spatula application. A: If left for 5 to 10 minutes, the putty composition begins to show an increase in viscosity, but to a level that does not cause any problems when applying with a spatula. D: In less than 5 minutes, the putty composition began to show an increase in viscosity, making application with a spatula difficult.

[0139] [Table 2-2]

[0140] The * in Table 2-2 is as follows:

[0141] (*12)Surface drying property: Each coated test plate (substrate 1: hot-dip galvanized steel plate) was left to stand at room temperature (20° C.) for a predetermined time, and then the surface dryness of each coated test plate was checked by touching with a finger.

[0142] S: After 20 minutes, the surface was good with no tack. A: After 25 minutes, the surface was good with no tack. D: After 30 minutes, there is tack on the surface.

[0143] (*13)Coating film hardness: Each test coated plate (substrate 1: hot-dip galvanized steel plate) was left at room temperature (20°C) for 12 hours, and then the coating hardness was examined using a Helmut Fischer FISCHERSCOPE HM2000S (conditions: maximum test force 1,000mN / 20 seconds and minimum test force 0.100mN / 5 seconds).

[0144] S: Martens hardness 80 or more, A: Martens hardness 60 or more but less than 80, D: Martens hardness less than 60.

[0145] (*14) Abrasiveness: Each test coated plate (substrate 1: hot-dip galvanized steel plate) was left at room temperature (20° C.) for 12 hours, and then polished with #400 waterproof paper, and the polished condition was evaluated.

[0146] S: Good, no clogging A: There is a very small amount of clogging, but it is not a problem for practical use. D: Clogged and heavy polishing.

[0147] (*15) Water resistance (bubble) Each topcoated plate (substrate 1: hot-dip galvanized steel plate) was immersed in water at 40° C. for 10 days, then removed from the water and the presence or absence of blisters on the surface of the coating film was observed.

[0148] S: No blisters on the entire coating surface. A: Some swelling is observed at the edge of the coating film or in the thin film, but it is not a problem for practical use. D: Significant blisters are observed over the entire coating film.

[0149] (*16)Water-resistant adhesion: The coated plates, which had been coated with a topcoat on the putty layer on each of the substrates 1 to 4 (hot-dip galvanized steel plate, mild steel plate, stainless steel plate, and aluminum steel plate) to form a topcoat coating layer, were immersed in water at 40°C for 10 days, then removed from the water and each coated plate was folded 180 degrees from the center to observe the coating condition at the folded part.

[0150] S: No peeling of the putty coating was observed. A: The putty coating has peeled off very slightly from between the steel plate and the putty, but this is not a problem for practical use. D: The putty coating film is significantly peeled off from between the steel plate and the putty.

Claims

1. pKa 2 an unsaturated polyester resin having an acid value in the range of 10 to 60 mgKOH / g, the unsaturated polyester resin comprising structural units of an acid component (a) containing a cyclic acid anhydride (a1) having a molecular weight of 5.8 or less and a hydroxyl group-containing component (b), the unsaturated polyester resin being a polyester resin having a radically polymerizable unsaturated group, a carboxyl group, and a hydroxyl group; the amount of the cyclic acid anhydride (a1) having a pKa 2 of 5.8 or less used is within the range of 1 to 50 mol % based on the total number of moles of the acid component (a); The unsaturated polyester resin is a polyester intermediate (X) having a carboxyl group and a hydroxyl group, and the pKa 2 2. An unsaturated polyester resin (A) which is obtained by half-esterification of a cyclic acid anhydride (a1) having a molecular weight of 5.8 or less.

2. As an acid source for the carboxyl group of the unsaturated polyester resin (A), 2 The unsaturated polyester resin (A) according to claim 1, wherein a cyclic acid anhydride (a1) having a molecular weight of 5.8 or less is used.

3. The unsaturated polyester resin (A) according to claim 1 or 2, wherein the acid component (a) further comprises methyltetrahydrophthalic acid and / or its anhydride.

4. The unsaturated polyester resin (A) according to any one of claims 1 to 3, wherein the acid component (a) contains an unsaturated polybasic acid and a saturated polybasic acid in a molar ratio of unsaturated polybasic acid / saturated polybasic acid in the range of 99 / 1 to 50 / 50.

5. The unsaturated polyester resin (A) according to any one of claims 1 to 4, wherein the hydroxyl group-containing component (b) contains a radically polymerizable hydroxy compound.

6. A putty composition comprising the unsaturated polyester resin (A) according to any one of claims 1 to 5.

7. A putty composition comprising the unsaturated polyester resin (A) according to any one of claims 1 to 5 and a polymerizable unsaturated compound (B), wherein the polymerizable unsaturated compound (B) contains a secondary hydroxyl group-containing polymerizable unsaturated monomer (b1) as a part of its components.

8. The putty composition according to claim 7, wherein the component (b1) is contained in an amount of 10 to 200 parts by mass per 100 parts by mass of the resin solid content of the unsaturated polyester resin (A).

9. The putty composition according to any one of claims 6 to 8, further comprising a dehydrating agent (C).

10. The putty composition according to any one of claims 6 to 9, which contains hollow particles (E).

11. A coating method comprising coating a putty composition according to any one of claims 6 to 10 on a surface of a substrate to form a putty layer.

12. The coating method according to claim 11, wherein the substrate surface is any one substrate surface selected from the group consisting of Shinkansen trains, railway cars, and automobile cars.

Citation Information

Patent Citations

  • Paint for decorative unsaturated polyester resin laminate

    JP1984109564A

  • Image forming device

    JP1994102753A

  • Resin composition

    JP2005162830A

  • Unsaturated polyester resin composition

    JP2005206781A

  • Unsaturated polyester resin composition and coating method using the same

    JP2006206863A